After blood diamonds: The moral economy of illegality in the Sierra Leonean diamond market - Nina Engwicht (Max Planck Institute for the Study of Societies, 2016)
While the role of illegal markets in contemporary inner-state wars has drawn considerable attention from both researchers and policy makers, very little is known about the fate of these "war economies" after the end of violent conflict. This paper aims to contribute to an understanding of the functioning of illegal markets under the condition of limited statehood by examining what has become of a notorious war economy: the illegal diamond market in Sierra Leone. Drawing on extensive field research, this analysis of the social order of the illegal diamond market in post-conflict Sierra Leone shows that while illegal activities are still widespread, the illegal diamond economy has largely been peacefully integrated into the social and economic order of the post-conflict society. In contrast to the violent and conflict-fueling war economy, the post-conflict illegal diamond economy is surprisingly benign. I argue that the illegal Sierra Leonean diamond market today can be understood as a moral economy of illegality, since economic action in this market is decisively shaped and regulated by widely held social norms about legitimate and illegitimate practices. It is highly interwoven with both the state and the legal markets, and has thus become part of the "peace economy." – – Während die Rolle illegaler Märkte in zeitgenössischen innerstaatlichen Kriegen erhebliche Beachtung in der Politikforschung und -praxis erfahren hat, ist nur sehr wenig über das Schicksal dieser "Kriegsökonomien" nach dem Ende gewaltsamer Konflikte bekannt. Dieses Diskussionspapier will zu einem Verständnis der Funktionsweise illegaler Märkte unter der Bedingung schwacher Staatlichkeit beitragen. Dazu wird ein illegaler Markt untersucht, der als typische Kriegsökonomie Berühmtheit erlangte: der illegale Diamantenmarkt in Sierra Leone. Basierend auf umfangreicher Feldforschung zeigt diese Analyse der sozialen Ordnung des illegalen Diamantenmarktes in der sierra-leonischen Postkonfliktgesellschaft, dass illegales Handeln auf dem sierra-leonischen Diamantenmarkt zwar immer noch weit verbreitet ist, sich die illegale Diamantenökonomie jedoch weitgehend friedlich in die soziale und ökonomische Ordnung der Postkonfliktgesellschaft integriert hat. Im Gegensatz zur gewaltsamen und Gewalt verstetigenden Kriegsökonomie ist der illegale Diamantenmarkt in der Nachkriegsgesellschaft überwiegend gewaltfrei. Der illegale Diamantenmarkt im heutigen Sierra Leone kann als "moralische Ökonomie der Illegalität" verstanden werden, da ökonomisches Handeln auf diesem Markt entscheidend durch soziale Normen der Legitimität und Illegitimität geprägt und reguliert wird. Indem der illegale Markt eng mit dem legalen Markt und dem Staat verwoben ist, wird er zum Teil der "Friedensökonomie".
Keywords: 300